Flexible hardware for teaching and research in renewable energy and off-grid microgrids - Cristian Escudero-Quintero; Juan Pablo Guzman-Rodriguez; Juan Pablo Villegas-Ceballos; Elkin Edilberto Henao-Bravo; Daniel Gonzalez-Montoya (HardwareX)
Microgrids are an active research field due to their integration of renewable and non-renewable energy sources alongside energy storage systems to supply both DC and AC loads. While existing studies extensively explore hierarchical control structures, focusing on algorithm design and optimization, practical implementation remains challenging due to system complexity. This paper presents the development of a low-power microgrid hardware platform based on power converters and controllers, enabling experimental validation of the second and third levels of hierarchical control. The platform enables real-time energy management using FPPT algorithms while providing an intuitive graphical interface for data visualization and system monitoring. Experimental results confirm the system’s capability of dynamically managing energy flows, ensuring stable operation under varying load conditions. The system demonstrates reliable operation handling loads of up to 100 W, with scalability to 200 W, providing an effective tool for testing and research in microgrid control strategies.